The Influence of Customer Relationship Management and Service Quality on Consumer Loyalty through Consumer Satisfaction - Salsabilah Wahyuni, Ratna; Rachbini, Widarto (Dinasti Publisher, 2024)
The development of the times has made companies providing online shopping services move to improve their services to be able to compete with competing companies. This research was conducted to find out whether there is an influence of customer relationship management and service quality on consumer satisfaction and consumer loyalty. This research uses data obtained from distributing questionnaires to 457 internet user respondents. The results of this research are that customer relationship management does not have a significant influence on consumer satisfaction and loyalty, while service quality has a significant influence on consumer satisfaction but has no effect on consumer loyalty.